DEVELOPMENT OF AN ANDROID-BASED RAIMA APPLICATION MEDIA TO IMPROVE STUDENTS' MASTERY OF CONCEPTS - Salsabila Aulia Putri; Ani Nur Aeni; Ali Ismail (Universitas Majalengka, 2024)
With the presence of technology, teachers must be able to balance and utilize technology in the learning process. One implementation of technology is the development of learning media. However, there is still a lot of learning in elementary schools that does not fully use technology-based media. All subjects, especially science subjects, require the use of media. This is because material science still contains abstract objects that are difficult to define. The aim of this research is to determine the feasibility and effectiveness of media on food chain materials in improving the concept mastery of fifth grade elementary school students. The R&D (Research and Development) method was used in this research, with the ADDIE development model which consists of five stages, namely: analysis, design, development, implementation, and evaluation. The research was carried out at one of the elementary schools in Rancaekek District, Bandung Regency, West Java, with research subjects involving material expert validators, media experts, teachers and 26 class V students. Data collection techniques in this research were interviews, observations, questionnaires and tests in the form of questions. tests given to students. This research resulted in a product in the form of an Android-based media application which was carried out a feasibility test by giving a questionnaire to validators and received a very feasible category. Then pretest and posttest results by design one group pretest-posttest, got significant results that show there is a difference in the results pretest and posttest, this means that student learning outcomes have increased. So it can be concluded that the product developed by researchers is very suitable for use as a learning medium and is able to improve students' mastery of concepts.